Electric vehicle machines and drives - Chau, K. T (Wiley, 2015)
Includes bibliographical references and index; Introduction -- DC Motor Drives -- Induction Motor Drives -- Permanent Magnet Brushless Motor Drives -- Switched Reluctance Motor Drives